Jaminan Hukum Bagi Warga Negara Untuk Hak Atas Pendidikan Agama Sebagai Fondasi Bagi Proses Pendidikan - Ni Ketut Tri Srilaksmi; Ambrosius M. Loho (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Education is an important factor to support government programs in realizing the ideals of the country. Education is an important factor for every subject. Character education for students can be integrated with formal, non-formal and informal education as a form of preventing juvenile delinquency. This character education is an effort to develop ethical, moral and responsible attitudes. Education as the initial foundation in supporting the realization of the ideals of this nation is also contained in the 1945 Constitution in Chapter XIII concerning Education and culture. The Indonesian government guarantees education to every citizen as stated in the 1945 constitution article 31 paragraphs 1 and 2 which states that every citizen has the right to education and every citizen is obliged to attend basic education and the government is obliged to pay for it. The Right to Education in the UDHR and the Human Rights Law sees humans from two different sides.